Development and quality evaluation of low fat Shrikhand from goat milk - kannan, radha; Shaji, Nima; Thomas, Sathian (Indian Journal of Dairy Science, 2018)
An effort was made to prepare low fat shrikhand from skimmed goat milk by utilizing whey protein concentrate (WPC) as a fat replacer. Control shrikhand samples were prepared from both whole goat milk (C1) and skimmed goat milk (C2).The prepared shrikhand samples were analyzed for physico â€“chemical and sensory qualities. There was no significant difference in pH, titratable acidity, total solids and ash content between the control and whey protein concentrate added Shrikhand samples. Â There was a significant increase in protein content in whey protein concentrate added sample when compared to control. No significant difference in sensory quality was observed between control and WPC added Shrikhand samples.